2019
DOI: 10.1186/s12970-019-0306-7
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific relationships among iron status biomarkers, athletic performance, maturity, and dietary intakes in pre-adolescent and adolescent athletes

Abstract: Background The purpose of this study was to examine relationships among biomarkers of iron status, athletic performance, growth and development, and dietary intakes in pre-adolescent and adolescent male and female athletes. Methods Two-hundred and forty-nine male (n = 179) (mean ± standard deviation for age = 12.0 ± 2.1 years, height = 156.3 ± 13.9 cm, and weight = 49.1 ± 16.5 kg) and female (n = 70) (12.0 ± 2.2 years, 152.4 ± 12.3 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 44 publications
1
4
0
1
Order By: Relevance
“…Additionally, approximately 28.6% of the studies reviewed in a systematic review of indoor team sport athletes met recommendations for protein while 50% did not; however, there was no delineation of differences for sex or sport [ 2 ]. Low protein intake is common in female athletes [ 13 , 45 ], which was also confirmed in this study ( Table 2 ). While not as important as a fuel source for performance, adequate protein is essential for muscle protein synthesis to tissue adaptations to training, recovery, and body composition changes, such as increased muscle mass [ 4 , 45 ].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Additionally, approximately 28.6% of the studies reviewed in a systematic review of indoor team sport athletes met recommendations for protein while 50% did not; however, there was no delineation of differences for sex or sport [ 2 ]. Low protein intake is common in female athletes [ 13 , 45 ], which was also confirmed in this study ( Table 2 ). While not as important as a fuel source for performance, adequate protein is essential for muscle protein synthesis to tissue adaptations to training, recovery, and body composition changes, such as increased muscle mass [ 4 , 45 ].…”
Section: Discussionsupporting
confidence: 88%
“…Several micronutrients have been highlighted as micronutrients of key interest for athletes, including iron, calcium, vitamin D, and antioxidants (including vitamins C, E, and beta-carotene) [ 4 ]. In general, all athletes had low intakes for these micronutrients, as well as many other vitamins and minerals analyzed in this study, with a specific concern for very low intakes of vitamin D and magnesium for all athletes, and iron and calcium in female athletes, which is an unfortunate common theme for female athletes [ 12 , 13 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In terms of performance, even mild tissue decrements in iron have the potential to adversely affect endurance capacity and aerobic adaptation to training [ 60 ]. Indeed, a recent study involving over 70 adolescent female athletes indicated a moderate relationship between athletic performance, the concentration of soluble transferrin receptors, and dietary iron intake, emphasizing the importance of iron intake for aspiring adolescent female athletes [ 61 ].…”
Section: Micronutrient Needs For Adolescent Athletesmentioning
confidence: 99%
“…In addition, Tsai et al reported that mildly anemic males enlisted within the Taiwan Military were likely to be the worst 10% performers during a standard 3000 m run test but were likely to be the best 10% performers during an anaerobic test such as the 2 min push-up test [170]. Shoemaker et al also indicated within youth athletic population that performance during aerobic fitness tests such as vertical jump, broad jump, agility drill times, 20-yard dash time, power push up force, were related to Hb status in males and with sTfR and iron intake in females [171]. Together these studies further support the notion that iron plays a role in aerobic metabolism and cardiorespiratory fitness; however, the role on iron status and anaerobic fitness tests require further investigation.…”
Section: Youthmentioning
confidence: 99%